(untitled) (Acta Entomologica Serbica, 2020)
Grasshoppers (Orthoptera: Caelifera) diversity were studied in three sites at different altitude in Jijel district (North East Algeria). The insects were captured with sweep net weekly from April to August 2016. It appears that 30 Grasshopper species belonging to 4 families and 11 subfamilies were identified amongst 712 individuals. Acrididae species (25) were the most frequent. The species richness was higher at medium altitude (23 species) and high altitude (22 species) than at low altitude (18 species). Species abundance distribution fitted the Broken stick model at low and high altitude while it fitted the Geometric or Motumura model at medium altitude. Grasshopper abundance increased with the altitude while diversity was not correlated with increasing altitude since diversity indices values were high in medium altitude.